Geochemistry of Surface Sediments From the Emperor Seamount Chain, North Pacific - Chen, Jie; Zou, Jianjun; Zhu, Aimei; Shi, Xuefa; Nürnberg, Dirk; Lembke-Jene, Lester; Tiedemann, Ralf; Wang, Kunshan; Wu, Yonghua; Dong, Zhi; Liu, Jianxing; Dou, Ruxi (Frontiers in Earth Science, 2021)
Investigating the composition and distribution of pelagic marine sediments is fundamental in the field of marine sedimentology. The spatial distributions of surface sediment are unclear due to limited investigation along the Emperor Seamount Chain of the North Pacific. In this study, a suite of sedimentological and geochemical proxies were analyzed, including the sediment grain size, organic carbon, CaCO3, major and rare earth elements of 50 surface sediment samples from the Emperor Seamount Chain, spanning from ~33°N to ~52°N. On the basis of sedimentary components, we divide them into three Zones (Ⅰ, Ⅱ and Ⅲ) spatially with distinct features. Sediments in Zone I (~33°N-44°N) and Zone III (49.8°N-53°N) are dominated by clayey silt, and mainly consist of sand and silty sand in Zone II. The mean grain size of the sortable silt shows that the hyrodynamic condition in the study area is significantly stronger than that of the abyssal plain, especially at the water depth of 1000-2500 m. The CaCO3 contents in sediments above 4000 m range from 20% to 84% but decrease sharply to less than 1.5% below 4000 m, confirming that the water depth of 4000m is the carbonate compensation depth of the study area. Strong positive correlations between Al and Fe, Ti, Mg and K (R>0.9) in the bulk sediments indicate pronounced contributions of terrigenous materials from surrounding continent mass to the study area. Furthermore, the eolian dust makes contributions to the composition of bulk sediments as confirmed by rare earth elements. There is no significant correlation between grain size and major and minor elements, which indicates that the sedimentary grainsize does not exert important effects on terrigenous components. There is significant negative δCe and positive δEu anomalies at all stations. The negative Ce anomaly mainly exists in carbonate-rich sediments, inheriting the signal of seawater. The positive Eu anomaly indicates widespread volcanism contributions to the study area from active volcanic islands arcs around the North Pacific. The relative contributions of terrestrial, volcanic, and biogenic materials vary with latitude and water depth in the study area.